Primary cerebral neuroblastoma: A case report and review - (:unkn) unknown (TOHOKU UNIV MEDICAL PRESS, 2002)
Primitive neuroepithelial tumors are the least common among supratentorial tumors in children. They pose great diagnostic difficulty, preoperatively as well as pathologically. Being quite rare, cerebral neuroblastomas are accepted as a distinct pathological entity, which differs from other neuroectodermal tumors, although clinically, radiologically, and morphologically at operation they are indistinguishable. Also differentiation between primary cerebral neuroblastoma and the other primitive neuroectodermal tumors may be difficult on light microscopy and be misleading. A 9-year-old girl with primary cerebral neuroblastoma who was initially misdiagnosed is reported. The other cases from the literature are reviewed and the nature of this rare tumor and its differential diagnosis is discussed. - primary cerebral neuroblastoma; primitive neuroepithelial tumors; childhood supratentorial tumors; neuropathological differential diagnosis (C) 2002 Tohoku University Medical Press.
Keywords: primary cerebral neuroblastoma; primitive neuroepithelial tumors; childhood supratentorial tumors; neuropathological differential diagnosis; PRIMITIVE NEUROECTODERMAL TUMORS; CENTRAL NERVOUS-SYSTEM; NEURO-BLASTOMA; CHILDREN; BRAIN